PENGUKURAN VALUE AT RISK MENGGUNAKAN PROSEDUR VOLATILITY UPDATING HULL AND WHITE BERDASARKAN EXPONENTIALLY WEIGHTED MOVING AVERAGE (EWMA) (Studi Kasus pada Portofolio Dua Saham) - Putri, Nurissalma Alivia; Hoyyi, Abdul; Safitri, Diah (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
Investment is an effort to get profits for individual or institution. But the investment policy is always faced with market risk as the effect of financial instruments movement such as stock price movements. Market risk measurement tool commonly used is Value at Risk (VaR), which measures the amount of loss at a certain confidence level. VaR measurement by Hull and White volatility updating procedure is a modification of the historical simulation involving information of volatility change calculated by Exponentially Weighted Moving Average (EWMA). This procedure is fit to financial data such as stock returns that are generally not normally distributed and are heteroskedastic. VaR calculation applied to the portfolio between Kalbe Farma Tbk (KLBF) stock and Lippo Karawaci Tbk (LPKR) stock from 3 January 2011 to 19 April 2013 were selected based on the largest trading volume at the end of the observation for LQ45 stocks listed in the Indonesia Stock Exchange (IDX) . The data used is the return calculated from the closing price of stocks. The validity of VaR was tested through a back test by Kupiec test, and concluded that the 95% VaR and 99% VaR are valid.